Design of portable drawing board / Mohd Asreen Ishak, Mohd Fauzi Ahmad and Mohamad Shihab Senik @ Abdul Mokhti - Ishak, Mohd Asreen; Ahmad, Mohd Fauzi; Senik @ Abdul Mokhti, Mohamad Shihab (2003)
This project has been design to fit to all sort of people. It does not matter either he is student, adults, or even corporate workers. However, our project main attraction is for secondary school student and the undergraduate students. “Portable drawing board” is the title of our project. From the title, we can bare in our mind that it is a board that easy to bring anywhere. Yes, that the main point, but to be more specific our design is a board the that is portable, multi function and not likely to be a burden drawing board like the resent drawing board which been used in schools nowadays. With the invention of this project, it can bring the student in more convenient and relaxing posture during doing their working in drawings. In another word this drawing board is a more ergonomics and affordable.